Spiritualitas Sains Modern: Pembacaan Terhadap Relasi Agama dan Sains - Mishbah Khoiruddin Zuhri (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
Modern science gets mixed responses from religious figures. This is motivated by a reading of religious text which is often inconsistent with recent scientific research. The advancement of science is not connected with the increase of spirituality. Spirituality becomes another dimension of science. In that situation, the integration theory of Ian G. Barbour tries to unravel the relation patterns of modern science and religion. There are four types of relationships: conflict; independent; dialog; and integration. This approach is rarely implemented in the realm of Islamic studies. This research seeks to implement the approach in Islamic studies by using descriptive-analytical method. I found the tendency of Muslim scientists more dominant in the exploration of Islamic studies than science. So the dominant relation between science and religion is a conflict; dialogue and natural theology. The underlying factor is the educational background of most of the Muslim scholars which is religious studies; limitations of interdisciplinary studies and lack of openness and renewal of views (tajdÄ«d) on religious texts.